2022
DOI: 10.1002/jcsm.12864
|View full text |Cite
|
Sign up to set email alerts
|

Development of ovarian tumour causes significant loss of muscle and adipose tissue: a novel mouse model for cancer cachexia study

Abstract: Background Cancer-associated cachexia (CAC) is a complex syndrome of progressive muscle wasting and adipose loss with metabolic dysfunction, severely increasing the morbidity and mortality risk in cancer patients. However, there are limited studies focused on the underlying mechanisms of the progression of CAC due to the complexity of this syndrome and the lack of preclinical models that mimics its stagewise progression. Methods We characterized the initiation and progression of CAC in transgenic female mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
(97 reference statements)
1
13
0
Order By: Relevance
“…Gdf9-iCre mice were purchased from the Jackson Laboratory. Mice carrying a floxed allele for Pik3ca * , Abl1 , or Trp63 were generated as previously described ( 10 , 11 , 19 , 58 ). All procedures involving mice were approved by the Institutional Animal Care and Use Committee at the University of Nebraska Medical Center (UNMC).…”
Section: Methodsmentioning
confidence: 99%
“…Gdf9-iCre mice were purchased from the Jackson Laboratory. Mice carrying a floxed allele for Pik3ca * , Abl1 , or Trp63 were generated as previously described ( 10 , 11 , 19 , 58 ). All procedures involving mice were approved by the Institutional Animal Care and Use Committee at the University of Nebraska Medical Center (UNMC).…”
Section: Methodsmentioning
confidence: 99%
“…360 Furthermore, dynamic wasting of BAT can be captured by a dedicated high-Fifield (7 Tesla) Bruker 7T ClinScan MRI combined with an infrared camera in the ovarian tumor mouse model. 361 Unfortunately, the information about MRI identifying thermogenic fat in clinical patients with malignancy is little.…”
Section: The Developmental Origin and Anatomical Location Of Thermoge...mentioning
confidence: 99%
“…When tumors are developing, cytokines, hormones, neuropeptides/neurotransmitters and tumor-derived factors can play a role in alliterating the metabolism of the adipose tissue throughout the body, such as inducing mitogen-activated protein kinases and the mitogen-activated protein kinase cascade reaction, thereby activating the p38 MAPK pathway [ 43 , 44 ]. Luan Y et al reported that mice with CAC showed significant activation of the p38 MAPK pathway and increased thermogenesis in the adipose tissue with high UCP1 expression [ 45 ]. It was also reported that lipolysis induced by pancreatic cancer exosomes could be attenuated in the presence of the p38 MAPK inhibitor (SB203580) in 3T3-L1 and human adipocytes [ 46 ], suggesting that p38 MAPK inhibitors help slow the lipolysis of fat.…”
Section: Discussionmentioning
confidence: 99%